PERAN PUBLIK PEREMPUAN DALAM PARLEMEN (STUDI ANALISIS REPRESENTASI WAKIL RAKYAT PEREMPUAN DALAM LINTAS SEJARAH INDONESIA) - Zahra, Fatimatuz (PALASTREN: Jurnal Studi Gender, 2014)
Keterwakilan perempuan dalam parlemen menjadi sebuah kebutuhan tak terelakkan, sebab berbagai problematika mengenai perempuan harus dan bisa diatasi oleh perempuan itu sendiri. Pada pemilu pertamadalam sejarah Indonesia 1955, perempuan bukanhanya punya hak pilih dan memilih, tetapi bahkan ada partai perempuan yang turut bertarung, yakni Partai Wanita Indonesia/Partai Wanita Rakjat. Dalam pemiluitu, ada 19 perempuan yang terpilih sebagai anggotaparlemen (DPR). Kebijakan kuota 30% perempuan yang diberlakukan mulai tahun 2004 justru banyak sekalianggota legislatif perempuan yang berperan sebagai“ganjal kursi” supaya partai tersebut lolos affirmative account. Artikel ini mengkaji analisis representasi wakilrakyat perempuan dalam persentase vokalitas serta peran aktif wakil rakyat perempuan tersebut dalam menyelesaikan berbagai persoalan bangsa menyangkut perempuan.Kata kunci: Keterwakilan, perempuan, analisis representasi The representation of women in parliament becomes an inevitable requirement, since various problems concerning women should and could be overcome by women themselves. History has proven in the 1955general election, the first election in the history of Indonesia, women not only have the right to vote andchoose, but even there the women who participatedfight party, namely the Indonesian Women Party / PartyWomen People. In the election, 19 women were electedto parliament (DPR). Since 2004, formally enacted Actrequirement for any political party that put forward legislative candidates who will compete in the elections,mandatory composition is 30% female and 70% male.This is precisely, makes the boomerang at a later date,with this requirement actually a lot of women legislatorswho serve as «padding seat» in order to qualify foraffirmative account of the party. And later on, whenthey were elected precisely is not based on an intentionto fight for women in various domains. Starting payattention to these problems, the authors moved to writeabout the analysis of the representation of the femalerepresentatives. Percentage vokalitas and the active roleof women representatives of the nation in solving variousproblems relating to women.Keywords: representation, women in parliament, paddingseat